2010
DOI: 10.5513/jcea01/11.4.856
|View full text |Cite
|
Sign up to set email alerts
|

Variability, Heritability and Correlations of Egg Shape in the Zatorska Goose

Abstract: The experiment was aimed at the evaluation of inheritance of goose egg measurements, egg shape indices and egg weight as well as the relationship between these traits. The research was carried out in the flock of the Zatorska geese, belonging to the FAO registered genetic resources of poultry. Seven hundred sixty-one eggs from pedigree bred geese in their first to fourth reproduction seasons were included in the analysis. Average egg shape index was 68.8%, average shell surface area was 140.6 cm 2. Egg weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…The differences between values obtained in the present study and the other studies were associated with the fact that the geese used in this study had different breed, age, origin, and egg weight and were reared under breeder conditions. The shell surface area of the present study was lower than the values (139.8, 141.5, and 134.6 cm 2 ) reported by Mazanowski and Adamski [4] for White Italian × Cuban geese in early, peak, and late periods and the value (140.60 cm 2 ) declared by Rabsztyn et al [26] for Zatorska geese. Mazanowski and Adamski [4] reported that the laying period had no effect on shell density in White Italian × Cuban geese.…”
Section: External Quality Traitscontrasting
confidence: 84%
“…The differences between values obtained in the present study and the other studies were associated with the fact that the geese used in this study had different breed, age, origin, and egg weight and were reared under breeder conditions. The shell surface area of the present study was lower than the values (139.8, 141.5, and 134.6 cm 2 ) reported by Mazanowski and Adamski [4] for White Italian × Cuban geese in early, peak, and late periods and the value (140.60 cm 2 ) declared by Rabsztyn et al [26] for Zatorska geese. Mazanowski and Adamski [4] reported that the laying period had no effect on shell density in White Italian × Cuban geese.…”
Section: External Quality Traitscontrasting
confidence: 84%
“…Similarly, Razmaite et al (2014) Bednarczyk and Rosiñski (1999). Rabsztyn et al (2010) have reported considerably smaller average egg mass of approximately 165 g of the autochtonous Zator goose (Poland), and Scripnic and Modvala (2010) report the average egg mass of the Italian White goose of 160 g.…”
Section: The Data Inmentioning
confidence: 93%
“…The following authors have significantly contributed to establishing genetic and non-genetic factors influencing incubation values of goose eggs and gosling quality: Meir and Ar (1991), Bednarczyk and Rosiñski (1999), Mazanowski and Chelmonska (2000), Rosiñski (2000), Mazanowski and Adamski (2002), Bobko and Svetlik (2002), Pakulska. (2003) Saatci et al (2005), as well as: Mazanowski and Bernacki (2006), Meir and Ar (2008), Ðermanovic et al (2008), Rachwal (2008), Rabsztyn et al (2010), Scripnic and Modvala (2010), RazmaitP et al (2014), Kucharska-Gaca et al (2016a), Kucharska-Gaca et al (2016b), Mitrovic et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…The average length of goose eggs varies between (approximately) 8 cm to 10 cm (Paganelli et al 1974;Rabsztyn et al 2010;Nedomova and Buchar 2014;Kumbar et al 2016;Ahmad et al 2017;Sreten et al 2018;Onk and Kirmizibayrak 2019), the width averages vary between 5 cm to 6 cm (Rabsztyn et al 2010;Nedomova and Buchar 2014;Kumbar et al 2016;Ahmad et al 2017;Sreten et al 2018;Onk and Kirmizibayrak 2019), and the shape index averages vary between 65 cm and 69 cm (Saatci et al 2002;Saatci et al 2005;Rabsztyn et al 2010;Nedomova and Buchar 2014;Kumbar et al 2016;Sreten et al 2018;Onk and Kirmizibayrak 2019).…”
mentioning
confidence: 99%
“…Paganelli et al (1974) calculated the egg shell surface area as 146.15 ± 7.08 cm 2 depending on the egg weight of Embden geese. The average volume of goose eggs varies between approximately 125 cm 3 to 175 cm 3 (Paganelli et al 1974;Saatci et al 2002;Nedomova and Buchar 2014;Kumbar et al 2016) and the average surface area varies between approximately 135 cm 2 to 150 cm 2 (Paganelli et al 1974;Rabsztyn et al 2010;Nedomova and Buchar 2014;Kumbar et al 2016). Paganelli et al (1974) calculated the volume of Embden geese as 158.74 ± 10.95 based on the egg weight.…”
mentioning
confidence: 99%